PC.10 Neonatal outcomes of singleton and multiple births at 32–36 Weeks of Gestation: Results from the Late And Moderately preterm Birth Study (LAMBS). (9th June 2014) - Boyle, EM; Johnson, S; Draper, ES; Manktelow, B; Seaton, S; Evans, TA; Smith, LK; Marlow, N; Field, DJ
Abstract : Background: There is a paucity of recent, prospectively collected data comparing outcomes between singletons and twins born at late and moderately preterm (32–36 weeks; LMPT) gestations. Methods: In a prospective, geographically defined, population-based study of babies born at 3236 weeks gestation we compared neonatal outcomes in normally formed singletons and multiples. Results: We recruited 200 LMPT and 274 term-born multiples, together with 907 live-born LMPT singletons. Within the LMPT group a greater proportion of singletons than multiples had jaundice (9.3% v 6.5%; P = 0.049) and hypoglycaemia (21.9% v 15.5%; P = 0.055). Other outcomes were similar between groups. Among multiples, those born LMPT were more likely to require resuscitation at birth (20.5% v 11.3%; P = 0.007), neonatal unit admission (43.0% v 8.4%; P < 0.001) and respiratory support (28.0% v 0.7%; P < 0.001). There were higher rates of jaundice (15.5% v 1.5%; P > 0.001) and hypothermia (6.5% v 2.6%; P = 0.042) in LMPT multiples and breast-feeding at discharge was lower (53.5% v 64.6%; P = 0.018) compared with term-born multiples. Conclusions: Our results suggest that many neonatal outcomes are similar between singletons and multiples and but some morbidities are reduced in multiples. LMPT multiples have poorer outcomes than their term-born counterparts. Differing maternal health, socioeconomic status, and indications for delivery in singletons and twins are likely to be key influences on neonatal outcome; postnatal management may also be important. Further analysis will explore factors contributing to birth at 32–36 weeks of gestation and neonatal outcomes. Follow-up will be crucial to determine any differences in long-term outcome related to prematurity or plurality.